(untitled) (Contemporary Issues on Indonesian Human Rights Law and Policy, 2024)
Indonesia is one of the few Southeast Asian nations that still retains the death penalty, with significant implications for human rights. This paper critically examines the human rights impact of Indonesia’s continued use of capital punishment, specifically in relation to international human rights norms and the debate over its abolition. The study analyzes legal documents, case law, and international human rights reports to assess how Indonesia’s retention of the death penalty aligns with or contradicts global human rights standards. It also reviews arguments made by proponents of the death penalty, including deterrence and justice for victims, alongside the criticisms regarding wrongful convictions, disproportionate punishment, and international condemnation. The research highlights the tensions between national sovereignty and international human rights pressures, offering a nuanced perspective on Indonesia’s stance on capital punishment. This study provides an essential critique of Indonesia’s death penalty policy, contributing to the broader discourse on human rights, criminal justice, and the ethics of capital punishment. By exploring Indonesia’s retention of the death penalty, the paper contributes to global human rights debates, offering policy recommendations that challenge the practice and encourage alignment with international human rights principles.